The Language of Agrarianism in Manitoba, 1890-1925 - Taylor, Jeffery (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1989)
Abstract Manitoba agrarianism underwent a change during the settlement and post-settlement period as a nineteenth century oppositional vision was displaced by an accommodationist position in the twentieth century. This article delineates this change by reconstructing the language of radicalism employed by the Patrons of Industry and the language of accommodation that became pre-eminent in the Manitoba Grain Grower"s Association and the United Farmers of Manitoba. It is suggested that, by viewing these languages as distinct entities with their own discursive unity, it is possible and necessary to view agrarian ideology at some distance from its putative class location.